2021
DOI: 10.3233/jvr-201118
|View full text |Cite
|
Sign up to set email alerts
|

Differential vocational rehabilitation service patterns and outcomes for transition-age youth with specific learning disabilities: Implications in the COVID-19 era

Abstract: BACKGROUND: It is essential to ensure that youth with specific learning disabilities (SLD) receive an appropriate type and amount of vocational rehabilitation (VR) services to facilitate their entrance to employment and career development. METHODS: In this study, the chi-squared automatic interaction detector (CHAID) analysis and multivariate logistic regression analysis were used to investigate the relationship among demographic variables, VR services, and employment outcomes for transition-age youth with SLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Some research shows that working from home is more prevalent in industries involving more highly educated and higher-paid workers and is less prevalent in lower-paid positions and in certain sectors (i.e., manufacturing, health care, retail) [54]. Youth with disabilities who are employed often work in entry-level positions such as restaurant and retail jobs, which were among the first industries to close down during the pandemic [39]. Those who remained employed in in-person positions during the pandemic often worked in high-risk sectors such as grocery stores or in health care [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research shows that working from home is more prevalent in industries involving more highly educated and higher-paid workers and is less prevalent in lower-paid positions and in certain sectors (i.e., manufacturing, health care, retail) [54]. Youth with disabilities who are employed often work in entry-level positions such as restaurant and retail jobs, which were among the first industries to close down during the pandemic [39]. Those who remained employed in in-person positions during the pandemic often worked in high-risk sectors such as grocery stores or in health care [39].…”
Section: Discussionmentioning
confidence: 99%
“…Youth with disabilities who are employed often work in entry-level positions such as restaurant and retail jobs, which were among the first industries to close down during the pandemic [39]. Those who remained employed in in-person positions during the pandemic often worked in high-risk sectors such as grocery stores or in health care [39]. Additionally, recent evidence shows the influence of the pandemic on people's mental health, resulting from a fear of catching the virus, dying, confusion, anger, and loss of employment [49], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study was unable to determine if this was also a factor as to whether Veterans were not accepted into the program (eg, perhaps they disclosed they were not interested in pursuing employment and wanted to be in the TW program that provides tax-free payments). Additionally, the impact of COVID-19 may explain disparities in employment rates at closure during the post-implementation phase of Policy Directive 1163, as a little over 1 year the COVID-19 pandemic changed the landscape of the United States, and Vocational Rehabilitation service delivery models in the public sector [25][26][27][28][29][30] and the implementation of telemedicine (VA Video Connect) occurred during the COVID-19 pandemic. [31][32][33]…”
Section: Limitationsmentioning
confidence: 99%
“…Pandemic-related employment disparities were greater for employees with disabilities who were also people of color than their White peers (Schall et al, 2021). Recent research has also found that transition-aged youth with multiple VR services delivered in a shorter period of time are more likely to have positive outcomes in employment, suggesting that correcting a pandemic-related absence of services could be redressed (Kaya et al, 2021).…”
Section: Introduction 29mentioning
confidence: 99%